Device for the standard measurement of shoot ﬂammability in the ﬁeld - Jaureguiberry, Pedro (2011)
Fire ecology has been hindered by the lack of comparable, affordable protocols to quantify the ﬂammability of whole plants over large numbers of species.We describe a low-tech device that can be carried to the ﬁeld and that allows highly standardized measurement of the ﬂammability of whole individuals or portions up to 70 cm long.We illustrate its potential with results for 34 species belonging to different growth forms from central Argentina. The device consists of an 85 ¥ 60 cm half-cut metallic barrel placed horizontally and mounted on a removable metallic structure. It contains three parallel burners, a grill with an attached gauging thermometer and a blowtorch. Burners and blowtorch are connected to a propane?butane gas cylinder. Plant samples are placed on the grill and preheated with the burners for 2 min at 150°C.They are then ignited for 10 s with the blowtorch while the burners are kept on. Four parameters are measured for each sample: maximum temperature reached, burning time, burnt length and burnt biomass percentage. These parameters are used to construct a compound index of ﬂammability for each sample that ranges between 0 (no ﬂammability) and around 3 (maximum ﬂammability).We obtained a wide range of values for ﬂammability and all its components. Most of this variability was accounted for by differences between growth forms and species, rather than by differences at the level of replicates.This suggests that the device and protocol are sensitive enough to detect ﬂammability differences among plants with different functional traits, and at the same time robust enough to produce consistent results among samples with similar traits. A major advantage is that plant architecture is kept almost intact, providing a ﬂammability measure much closer to that of whole individuals in the ﬁeld than those obtained by other standard protocols in use. The device and protocol presented here should facilitate the acquisition of comparable ﬂammability data over large numbers of species from different ﬂoras and ecosystems, potentially contributing to several ﬁelds of research, such as functional ecology, evolutionary ecology and vegetation-atmosphere modelling.